Medication Error at the Prescribing Phase - Devi Ristian Octavia; Slahayu Niken Purwandini; Maria Hilaria; Dimas Prayogo Pangestu (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Medication errors are accidental failures in a therapeutic process that lead to and have the potential to cause or harm the patient. Medication errors can endanger patient safety, inconvenience and economic burdens. Medication errors can occur at the prescribing, recording, issuing, and administering stages. Reducing the risk of medication errors is a shared responsibility among patients, healthcare professionals, regulators and the pharmaceutical industry at all levels of healthcare delivery. This research is a quantitative research with a descriptive approach. The population taken was 912 prescriptions written by general practitioners at the PKU Muhammadiyah Cepu Hospital in March-May 2019. The sampling technique used was non-probability sampling, which was total sampling. The instrument used in this study was an observation sheet, then the collected data were processed by editing, coding, scoring, and tabulating stages which were then concluded descriptively. The results showed that the incidence of drug prescribing errors in inpatients at PKU Muhammadiyah Cepu Hospital in March 2019 found that all written prescriptions were 100% administratively incomplete. The incidence of prescription medication errors, especially the doctor's name, was 65.9%, the doctor's practice license number was 100%, the date of the prescription was 48.9%, the sign of R/70.9%, the doctor's initial 48.7% and the patient's address 97.4%. Incomplete administrative prescription writing can result in medication errors that are detrimental to health and add to the economic burden of patients.